Thermochemical conversion of sewage sludge for energy and resource recovery: technical challenges and prospects. Issue 1 (1st January 2021) - Hu, Mian; Ye, Zhiheng; Zhang, Haiyang; Chen, Baixiao; Pan, Zhiyan; Wang, Junliang
ABSTRACT: Thermochemical processes are considered as a promising technology for sewage sludge management, which could achieve volume reduction, energy and resource recovery, and effective destruction of pathogens. However, there are still many technology limitations and challenges of the thermochemical processes toward industrialization and commercialization. This review first briefly discusses the impact of sewage sludge on environmental sustainability and its current treatment and disposal methods. Typical thermochemical conversion technologies i.e., incineration/combustion, pyrolysis, gasification, and hydrothermal liquefaction for energy and resource recovery from sewage sludge are then comprehensively summarized. Subsequently, the technical challenges of thermochemical conversion of sewage sludge and the solutions that have been and/or are being developed to address the challenges are in-depth analyzed. Meanwhile, the prospects and future directions of the thermochemical technologies are outlined. In addition, the economic analysis and life cycle assessment of thermochemical conversion technologies are evaluated. Finally, the conclusions are put forward.